EFFECT OF DIGESTIVE SYSTEM OF SOME RUMINANT ANIMALS IN BREAKING DORMANCY OF ACACIA NILOTICA SEEDS - Jibo, A. U.; Salami, K. D.; Muhammad, Y. K. (FUDMA Journal of Sciences, 2023)
Seeds of some plant species have hard, cutinized seed coats that completely prevent the inhibitions of water and sometimes also the exchange of gases. Dormancy in nature serves to protect the seed from conditions which are temporarily suitable for germination. However, where dormancy is strong, some form of seed pre-treatment is essential in artificial regeneration, in order to obtain a reasonably high germination rate in a short time. Seeds of some species are said to be regurgitated after partial rumination. Feeding the pods of Acacia nilotica through the digestive system of some animals (sheep and goat) and collecting the seeds from the droppings as a convenient pre-treatment to overcome seed coat dormancy. After digestion, four hundred (400) treated seeds were collected from the feacal of both animals by washing with distilled water and placed on moist cotton in a petri dish. The results revealed that 80 % of seeds passing through the digestive system of (sheep and goat) had higher germination rate.
Keywords: Acacia nilotica, Digestive system, Dormancy